Inside US spy satellites - Baker, David, 1944- (Geek's guide to espionage and warfare., 2019)
Explores the history, technology, and evolution of U.S. spy satellites. Also looks at the science behind various types of satellites, and provides in-depth analysis of their internal specifications and abilities. Includes color photographs, a glossary, and further resources.